2016
DOI: 10.4152/pea.201606365
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Aluminum by Psidium Guajava Seeds in HCl Solution

Abstract: The corrosion inhibition and adsorption of ethanol extracts of Psidium guajava seeds (EEPgS), for aluminum in 0.5 N HCl solutions, were investigated using conventional weight loss, FTIR spectroscopy and SEM analysis techniques. The results showed that EEPgS performed well as inhibitor for the corrosion of aluminum in hydrochloric acid media. FTIR results showed that the inhibition mechanism was by adsorption process, through the functional groups present in the extract. Inhibition efficiency increased with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…This is due to the interplay between the additive molecules and the Al surface through their functional groups. 63 Neither the disappearance of peaks nor the appearance of any new peaks on the spectrum of Al in 4 M NaOH with 2.0 g l −1 of extract compared to the spectrum of collard greens powder was observed. This indicates that it does not involve either the formation of new chemical bonds or the chemical interactions between this extract additive and the Al surface.…”
Section: Inh Adsmentioning
confidence: 89%
“…This is due to the interplay between the additive molecules and the Al surface through their functional groups. 63 Neither the disappearance of peaks nor the appearance of any new peaks on the spectrum of Al in 4 M NaOH with 2.0 g l −1 of extract compared to the spectrum of collard greens powder was observed. This indicates that it does not involve either the formation of new chemical bonds or the chemical interactions between this extract additive and the Al surface.…”
Section: Inh Adsmentioning
confidence: 89%
“…The decrease in the CR is due to the mitigating effect of the PE on the metal specimens [6].The IE was found to decrease as the temperature was increased from 303 K to 323 K. This shows that the adsorption of PE on the metal surface may be due to physical adsorption [7]. The high surface coverage data also implies that the adsorption of PE at the Aluminium interface may be due to the electrostatic force between the atoms on the metal surface and the adsorbate (inhibitor molecules) [8]. By plotting the values of θ versus log C and C/θ values versus C, straight line graphs were obtained (Figure 3 and 4), which showed that Temkin and Langmuir adsorption isotherms are obeyed.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…At once, methanol extract (800 ppm) of P. guajava leaves acts as a good corrosion inhibitor with maximum efficiency of about 89% for mild steel in 1 M phosphoric acid. [ 30 ] Similarly, the extract of guava ( P. guajava ) leaves acts as a mixed inhibitor for mild steel [ 31 ] and aluminum [ 32 ] corrosion control in a HCl solution. Tannin isolated from P. guajava leaves enhanced the corrosion protection of stainless steel in HCl and enhanced about 92% inhibition efficiency.…”
Section: Introductionmentioning
confidence: 99%